Movement Disorders - Lazzarotto, DO, Mana; Keenum, DO, PharmD, Amy J.; Januchowski, DO, FACOFP, Health Literacy Editor, Ronald (Osteopathic Family Physician, 2017)
Movement disorders affect about 28% of the U.S. population aged 50-89. They are conditions that affect how we move. The most common movement disorder is an essential tremor. An essential tremor usually affects the hands. It is an unwanted shaking that is present at rest and worsens with movement. Your doctor can help the symptoms with medication. Another movement disorder is Parkinson’s Disease, affecting 10 million people. It is caused by the brain being unable to produce a substance called dopamine. The symptoms start gradually and include tremor, which progresses to stiffening of the muscles. There may be a genetic component to Parkinson’s Disease, but some people are affected without having a family history. There are medications and therapies that can help slow down the progress of the disease and symptoms; however, there is no cure.